Interaction in the EFL Speaking Class - Yosefa J. Mariono (Widya Mandala Surabaya Catholic University, 2011)
This paper is focused on classroom interaction related to the problems faced by EFL students in the Speaking class, highlighting the teacher’s role to direct classroom interaction to promote cooperative and supportive learning environment. Varied kinds of interactive learning activities are presented to engage the students in active participation